Understanding Business Potential For Solar Products For Rural Area - et. al., Prof. Priyadarshani Zanjurne, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Solar has been identified as one of the key renewable sources to supplement the conventional energy sources and reduce carbon footprint in India. Solar power business in India is indulging. The opportunity in this sector is vigorous and exalting. In this paper researcher has tried to through highlights on business potential for solar products with special reference to residential area/rural area. Solar energy has the potentiality of expanding into large scale operations and fulfills the industrial and domestic use. The objective heading of this paper is to understand business potential of solar energy. Researchers have chosen few best business opportunities and ideas for the rural peoples those are willing to start their business with solar products.